An illustrated history of the First World War - Keegan, John 1934-2012 (A.A. Knopf, 2001)
From a premier military historian comes a stunningly illustrated volume incorporating an abridged text of his bestselling "The First World War." Full color and b&w. Now Keegan has gathered together 475 photographs, maps, & other illustrations that allow us to see what his text so brilliantly describes: the startling ferocity of the conflict; the hellish nature of the trenches; the legendary battles of Flanders, the Somme, Verdun, Gallipoli, & their aftermaths; the tanks, submarines, & airplanes new to the battlefield; the faces of the statesmen who made the war & the soldiers who fought it. Together, text & illustrations give us the most comprehensive & illuminating history we have of the First World War, the progenitor of all 20th-century warfare. John Keegan's The First World War was everywhere praised, and became the definitive account of the war that created the modern world
The text is an abridgment of the author's The First World War. - Includes bibliographical references (p. 411-414) and index
Keywords: Geschichte; Guerra Mundial, 1914-1918; Weltkrieg (1914-1918); World War, 1914-1918; Erster Weltkrieg